2013
DOI: 10.1007/s12529-013-9299-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Physical Effort, Fatigue, and Mental Distress in Patients with Coronary Artery Disease: Importance of Personality-Related Differences

Abstract: Type D personality traits independently predicted poor functional status and worse patient-centered outcomes independently from LVEF and depression. Further studies exploring personality-related differences in cardiovascular outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…This supports the notion that the SI-component, in combination with NA, further increases the risk of depression. This is also in line with previous research among people with coronary artery disease (Bunevicius et al, 2014) showing significant differences in cognitive-affective symptoms of depression between Type D subgroup and NA-only.…”
Section: Discussionsupporting
confidence: 93%
“…This supports the notion that the SI-component, in combination with NA, further increases the risk of depression. This is also in line with previous research among people with coronary artery disease (Bunevicius et al, 2014) showing significant differences in cognitive-affective symptoms of depression between Type D subgroup and NA-only.…”
Section: Discussionsupporting
confidence: 93%
“…The present study not only confirms these findings but also showed that it was the combined presence of social inhibition with high NA that was associated with chest pain. This biological interaction of Type D personality was further validated by the presence of significantly elevated depressive symptoms in the Type D group compared with the high NA group, which is consistent with findings in a CAD population (Bunevicius et al., ). However, further validation of these personality subtypes is needed.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have observed that the NA and SI components of Type D interacted to predict medication adherence (Williams et al., 2011a), and that Type D personality was associated with increased illness perception in patients with myocardial infarction (Williams et al., 2011b), and increased health care utilization in the general population (Michal et al., ). Moreover, Type D personality, but not the other personality subtypes, showed decreased exercise capacity and motivation in CAD patients (Bunevicius et al., ), which can be hypothesized to have adverse effects on health in nonobstructive CAD patients as well.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our final study sample consisted of 523 patients. Data on personality related differences and on evaluation of depression in this cohort of patients were previously published elsewhere [17,24-28]. …”
Section: Methodsmentioning
confidence: 99%